Study on prediction of blasting cracking radius of liquid CO2 in coal. - Jinzhang Jia; Yumo Wu; Dan Zhao; Bin Li; Dongming Wang (PLoS ONE, 2023)
In this study, we sought to improve the efficiency of coal seam gas extraction, master the characteristics of different factors on the liquid carbon dioxide (CO2) phase change blasting cracking radius, and effectively predict the hole spacing. In this study, we used ANSYS/LS-DYNA numerical simulation software to predict the crack radius of liquid CO2 phase change blasting combined with orthogonal design scheme. The results showed that the primary and secondary factors affecting the fracture radius of liquid CO2 phase change blasting were in ground stress, gas pressure, coal firmness coefficient, and gas content. The fracture radius decreased with the increase of in ground stress and decreased with the increase of gas pressure, coal firmness coefficient, and gas content, which was linear. A prediction model for predicting the cracking radius of liquid CO2 phase change blasting based on four groups of different factors was established. Through the double verification of numerical simulation and field industrial test, the cracking radius of liquid CO2 phase change blasting ranged from 2 m to 2.5 m. The maximum error of numerical simulation was 2.8%, and the maximum error of field industrial test was 5.93%.